Justice and health care rationing in AUGE: bioethical dilemmas associated to the distribution of scarce resources - Zúñiga Fajuri, Alejandra (Acta Bioethica, 2011)
Rationing criteria in health care establish by AUGE, in Chile, are based, mainly, in maximum efficiency, contrary to the equity principle, which should sustain health care policies in democratic societies. For the application and justification of health care rationing techniques is required not only a medical science and health care economy reflection, but a moral philosophy and bioethical reflection as well. The study of health care distributive justice theories allows to value critically health care rationing criteria used by Clinical Guidelines for each GES/AUGE pathology, which operate contrary to the equity principle.